Shorter CAG repeat length in the AR gene is associated with poor outcome in head and neck cancer - Rosa, Fabiola Encinas; Mattos dos Santos, Rodrigo; Poli-Frederico, Regina Celia; Canevari, Renata de Azevedo; Nishimoto, Ines Nobuko; Magrin, Jose; Rainho, Claudia Aparecida; Kowalski, Luiz Paulo; Rogatto, Silvia Regina [UNESP] (Elsevier B.V., 2007)
Objective: Alterations in the size of the [CAG](n) repeats of the AR gene have been described in several types tumors. The purpose of this study was to evaluate if there is an association between the AR [CAG](n) repeat alleles and the relative risk for head and neck cancer and to analyse microsatellite instability (MSI) and loss of heterozygosity (LOH) in these tumors.Design: Matched samples of blood and head and neck tumors were evaluated using two methodologies, silver-stained gels to perform the analyses of MSI and LOH, and automated analysis to confirm these results and for genotyping of the AR [CAG](n), repeat length. Sixty-nine individuals without cancer were used as a control group for both procedures. The Log-rank test was used to compare overall survival and disease-free survival curves. The Cox proportional hazards regression models were performed to determine the [CAG], repeats as an independent prognostic factor.Results: Patients with alleles <= 20 in the male group showed a correlation with lower disease-free survival (P = 0.0325) and with recurrence or metastasis (RR 2.52, CI 95%). in the female group, the allele 2 (longer allele) showed a significant lower mean of [CAG](n), repeat when compared to the control group. Microsatellite instability was detected in nine cases in both procedures. In six out of these nine cases, we observed a reduction of the AR [CAG](n) repeat length. LOH was detected in one out of 17 women informative for oral cancer in both procedures.Conclusion: These results suggest that short [CAG](n) repeat length (: 20) polymorphism is associated with poor prognosis in a subset of male patients with head and neck cancer and that AR gene microsatellite instability is uncommon in these tumors. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: head and neck cancer; AR gene; [CAG](n) repeats; microsattelite instability